The impact of financial literacy on the uptake of commercial bank products and services in Zimbabwe - Manganda, James (Midlands State University, 2014)
Research has proven that financial literacy improves the knowledge, attitude towards and uptake of financial products and services. It is in this context that this research assessed the level of financial literacy amongst commercial bank clients in Zimbabwe. Moreover, given the failure in the past by the Zimbabwean banking sector to perform its role effectively due to issues such as bank failures, operational failures and the provision of expensive inappropriate products, the researcher examined the effect of financial literacy on the uptake of commercial bank products Zimbabwe. In order to achieve these main objectives, the researcher also looked at the effect of income and education on financial literacy and measured the level of uptake of commercial bank products in Zimbabwe. The researcher reviewed both theoretical and empirical literature on financial literacy and bank product uptake in order to make inferences and provide the basis for a strong analysis. Studies carried out in both developing and developed countries were incorporated in the empirical literature review and theories such as diffusion of innovations were used to provide a theoretical premise for this study.The researcher employed a descriptive research design in order to generate conclusive on the subject matter by using both qualitative and quantitative data. A sample of 87 bank clients and 5 bank personnel was drawn using both convenience and simple random sampling. The researcher found out that the general level of financial literacy amongst commercial bank clients in Zimbabwe is fairly high. The research also showed to a larger extent that income has a positive effect on individuals’ level of financial literacy. However this is not always the case as some respondents with low income demonstrated high levels of financial literacy. It was also noted that increased levels of education are associated with high levels of financial literacy also has a positive effect on individuals’. A fairly low uptake of banking products and services in Zimbabwe was discovered in this study although some of the bank personnel indicated high levels of uptake of their banks’ products and services. The major finding of this research was that financial literacy has a positive impact on the uptake of commercial bank products and services in Zimbabwe. However it was noted that other factors such as income, age and product costs also affect the uptake of bank products. In order to improve the uptake of products and services, commercial banks should incorporate financial literacy in their advertising complemented by incentive programs such as promotions and tailor made products. Furthermore, the study recommends the development and implementation of a financial literacy framework by a mandated authority for the improvement of the general level of financial literacy in Zimbabwe.